(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The integration of sustainability literacy into English for Specific purposes (ESP) instruction represents a vital pedagogical shift, moving beyond traditional language acquisition to foster a sense of global citizenship and environmental responsibility. While some educators may hesitate to broach controversial environmental topics, the necessity of equipping students with the knowledge to address real-world challenges like climate change is paramount. This approach, often termed green or sustainability education, enriches the learning process by making it more meaningful and engaging. By using environmental themes as the foundation for language practice, students not only enhance their linguistic competencies but also develop critical thinking and problem-solving skills. The article advocates for a Content-Based Instruction (CBI) model, which organizes language teaching around substantive environmental content. This method allows learners to use English for functional, real-world purposes, thereby transforming them into more informed and environmentally conscious individuals prepared for the demands of the modern service sector. The proposed lesson plan on the climate crisis exemplifies how to bridge theoretical knowledge with practical, discipline-specific application.